2003
DOI: 10.1161/01.res.0000101744.47866.d5
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycan Is a Mechanosensor on Endothelial Cells

Abstract: Abstract-The objective of this study was to test whether a glycosaminoglycan component of the surface glycocalyx layer is a fluid shear stress sensor on endothelial cells (ECs). Because enhanced nitric oxide (NO) production in response to fluid shear stress is a characteristic and physiologically important response of ECs, we evaluated NO x (NO 2 Ϫ and NO 3 Ϫ ) production in response to fluid shear stress after enzymatic removal of heparan sulfate, the dominant glycosaminoglycan of the EC glycocalyx, from cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
467
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 543 publications
(520 citation statements)
references
References 46 publications
30
467
0
14
Order By: Relevance
“…In the present investigation, we extend the in vitro study of Florian et al [9] by exposing BAECs to shear stress after treatment with heparinase, chondroitinase, hyaluronidase, and neuraminidase to selectively degrade key components of the glycocalyx (HS, CS, HA, SA, respectively). In addition to measuring NO production, we also measure the shear-induced production of prostacyclin (PGI 2 ).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the present investigation, we extend the in vitro study of Florian et al [9] by exposing BAECs to shear stress after treatment with heparinase, chondroitinase, hyaluronidase, and neuraminidase to selectively degrade key components of the glycocalyx (HS, CS, HA, SA, respectively). In addition to measuring NO production, we also measure the shear-induced production of prostacyclin (PGI 2 ).…”
Section: Introductionmentioning
confidence: 75%
“…Several studies in live animals or with intact vessels showed that depletion of SA [7,8] or HA (19)with enzymes abolished flow-dependent vasodilation or nitric oxide (NO) production. Florian et al [9] presented the first in vitro evidence that GAGs may mediate EC mechanotransduction. They used a heparinase enzyme to selectively degrade the HS component of bovine aortic endothelial cells (BAECs), and observed that the substantial production of NO induced by steady or oscillatory shear stress could be completely inhibited by a dose of enzyme that removed only 46% of the fluorescence intensity associated with a HS antibody.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronic acid is also the major component of glycocalyx, which is a hydrated proteoglycan layer covering the luminal aspect of EC Reitsma et al, 2007). Interestingly, glycocalyx production by EC is related to fluid shear stress and to atherosclerosis in hypercholesterolemic and hyperglycaemic patients (Wein- baum et Florian et al, 2003;van den Berg et al, 2006;Nieuwdorp et al, 2006). CD31 did not respond to fluid shear stress and served as a negative control.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from Mochizuki et al (Mochizuki et al, 2003; isolated canine femoral arteries) and Florian et al (Florian et al, 2003; cultured endothelial cells) disrupting components of the glycocalyx enzymatically prevented nitric oxide release. It would follow that if nitric oxide is released similarly in frog mesenteric capillaries, then the increased L p after pronase implies an antagonistic role for nitric oxide with regard to barrier function.…”
Section: Shear Stress Mechanotransduction and Clinical Significancementioning
confidence: 99%